1980
DOI: 10.1038/283865a0
|View full text |Cite
|
Sign up to set email alerts
|

HLA-restricted T-cell recognition of Epstein–Barr virus-infected B cells

Abstract: In mice the cytotoxic T-cell response to several types of virus is influenced by genes within the major histocompatibility complex; in particular, genetic control is exercised at the effector cell level through a requirement that virus-specific cytotoxic T cells recognise viral antigens in association with H-2K and H=2D region gene products on the surface of infected cells. In man the restriction which the analogous HLA-A, -B and -C-region gene products might place on virus-specific T-cell function is still in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
46
0

Year Published

1980
1980
1993
1993

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(47 citation statements)
references
References 19 publications
1
46
0
Order By: Relevance
“…Our findings of consistent self-preferred lysis of EBV-infected target cells, crossreactive cytotoxicity between donors sharing HLA-B specificities or carrying crossreactive HLA-B specificities, and selective inhibition of cytotoxicity by autologous and HLA-B-related competitor cells collectively provide strong evidence that immune cytotoxic T cell activity to EBV in humans is HLA-restricted. A similar conclusion has been reached by others, using an assay based on inhibition of outgrowth of target cells (13). Extensive competition experiments as well as family studies are needed, however, to substantiate and clarify the HLA-B-locus-linked crossreactivity observed in this work.…”
supporting
confidence: 51%
“…Our findings of consistent self-preferred lysis of EBV-infected target cells, crossreactive cytotoxicity between donors sharing HLA-B specificities or carrying crossreactive HLA-B specificities, and selective inhibition of cytotoxicity by autologous and HLA-B-related competitor cells collectively provide strong evidence that immune cytotoxic T cell activity to EBV in humans is HLA-restricted. A similar conclusion has been reached by others, using an assay based on inhibition of outgrowth of target cells (13). Extensive competition experiments as well as family studies are needed, however, to substantiate and clarify the HLA-B-locus-linked crossreactivity observed in this work.…”
supporting
confidence: 51%
“…Since recognition by CTL must be considered as a prima fade evidence for surface localization of an antigen, the actual relationship between these serologically detectable intracellular proteins and the antigen LYDIEA requires further analysis. The presence of nonglycosylated viral proteins, located predominantly in the nucleus and cytoplasm, coincides with the recognition of infected cells by CTL also in other virus infections such as EpsteinBarr virus 26 , simian virus 40 27 • 28 and influenza virus 29 -31 • In this context it has been suggested that processed products rather than the intact protein may represent the actual antigen 31 or that the intracellular protein may modify other viral or cellular products 29 • Irrespective of the so far unknown molecular identity of LYDIEA, the requirement of IE proteins for the synthesis of viral structural proteins during acute infection or after reactivation from latency raises the possibility of a physiological role of LYDIEA-specific CTL in the surveillance of viral latency. L YDIEA-specific memory-CTL which are present in latently infected mice 8 There is now good evideoce that cytoplasmic pH (PH;) may have an important role in the metabolic activation of quiescent cellsl,z.…”
mentioning
confidence: 81%
“…In contrast, CTL responses can be detected against viruses that establish latent or persistent infections, such as the herpesviruses (Yasukawa et al, 1989;Hickling et al, 1986;Rickinson et al, 1981) or human retroviruses (Walker & Plata, 1990;Kannagi et al, 1983;Mitsuya et at., 1983). Thus, the frequency of anti-VV CD8 + cells could drop to undetectable levels in the absence of periodic re-exposure to viral antigen through reinfection or reactivation of latent viruses.…”
Section: Short Communication 753mentioning
confidence: 99%